2021
DOI: 10.3390/ijerph181910495
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Work Engagement of Employees Working from Home during the COVID-19 Pandemic in Japan

Abstract: This study aimed to identify factors influencing the work engagement of employees working from home during the COVID-19 pandemic in Japan. Employees’ work engagement was examined using the following survey questions: “Do you feel energized when you are at work? (yes or no)” and “Do you take pride in your work? (yes or no)” After adjusting for potential confounders, Poisson regression was used to examine prevalence ratio and 95% confidence intervals for employees’ work engagement. We analyzed 15,670 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…One study established that high-quality telework (e.g., agile workplaces, virtual leadership) was associated with higher work engagement during the pandemic [38]; however, different results were obtained in a study conducted by [39], which found that high intensity telework was not associated with work engagement during the pandemic. We were also able to locate a study that concluded that among employees who worked from home during the COVID-19 pandemic in Japan, an increase in sleep hours, effective interactions with supervisors, and working less than 40 hours a week were associated with high work engagement [8]. Although not specifically focusing on work engagement, one study found that most people had a more positive than negative experience of working from home during the COVID-19 pandemic [40].…”
Section: The Role Of Teleworkingmentioning
confidence: 98%
See 1 more Smart Citation
“…One study established that high-quality telework (e.g., agile workplaces, virtual leadership) was associated with higher work engagement during the pandemic [38]; however, different results were obtained in a study conducted by [39], which found that high intensity telework was not associated with work engagement during the pandemic. We were also able to locate a study that concluded that among employees who worked from home during the COVID-19 pandemic in Japan, an increase in sleep hours, effective interactions with supervisors, and working less than 40 hours a week were associated with high work engagement [8]. Although not specifically focusing on work engagement, one study found that most people had a more positive than negative experience of working from home during the COVID-19 pandemic [40].…”
Section: The Role Of Teleworkingmentioning
confidence: 98%
“…Moreover, comprehending the moderating role of organizational and individual characteristics is important to better identify the optimal conditions in which to implement teleworking. Moreover, there is insufficient knowledge of the effect of new ways of working (e.g., working from home) on employees' engagement during the COVID-19 pandemic [8]. Long before the present context arose, former U.S. President Barack Obama mentioned the importance of attracting and retaining employees who are more productive and engaged via flexible workplace policies (e.g., working from home) [9].…”
Section: Introductionmentioning
confidence: 99%
“…The close communication with supervisors and colleagues, working hours of <40 h/week, and the absence of a mental disorder was associated with high work engagement in employees who worked from home and those who did not. However, Amano et al (2021) found factors such as unchanged opportunities for physical activity, unchanged and decreased sleeping hours, unchanged opportunities for eating breakfast, and working hours of greater than or equal to 40 h/week are independently associated with lower engagement for employees who worked from home. For example, the proportion of WFH employees who had increased their sleep duration had higher work engagement than those who experienced decreased sleep duration.…”
Section: Work-from-home Positive-negative Forces (+-)mentioning
confidence: 87%
“…An investigation of the change in sleeping hours, interactions with supervisors, and working hours of 3776 employees who worked from home compared to 11,894 employees who did not work from home in Japan indicated some similarities for both groups (Amano, Fukuda, Shibuya, Ozaki, & Tabuchi, 2021). The close communication with supervisors and colleagues, working hours of <40 h/week, and the absence of a mental disorder was associated with high work engagement in employees who worked from home and those who did not.…”
Section: Work-from-home Positive-negative Forces (+-)mentioning
confidence: 97%
“…This discrepancy may be attributable to the use of different indicators (company size vs. worksite size) or different survey years reflecting different economic situations. Working from home decreased employees’ communication with their supervisors and colleagues (Amano et al 2021). Therefore, working from home may affect the association between company size and psychological distress via communication changes.…”
Section: Discussionmentioning
confidence: 99%